THE MODERATING ROLE OF FINANCIAL LITERACY'S ON FINTECH, PAYLATER, ATTITUDE AND CONSUMPTIVE BEHAVIOR AMONG MILLENNIALS - Yuhasril Yuhasril; Hirdinis M.; Arief Bowo Prayoga Kasmo; Arinah Nurullita Mawaddah (Jurnal Bisnis dan Akuntansi, 2026)
The rapid digitization of financial services, particularly "Buy Now, Pay Later" (BNPL) products like Shopee PayLater, raises concerns about unsustainable spending, especially among tech-savvy millennials. Grounded in a post-positivist philosophy, this study investigates whether financial literacy acts as a protective moderator, weakening the positive influence of general financial technology (FinTech) adoption and specific Shopee Pay-Later use on consumptive behavior. A prudential-financial attitude was incorporated as a direct antecedent to provide a holistic model. Data were collected via a structured survey from 150 purposively sampled millennials (aged 20-45) in Tanjung Priok, Jakarta, who are active digital commerce users. The hypotheses were tested using Partial Least Squares Structural Equation Modeling (PLS-SEM). The results confirmed that FinTech adoption, Shopee PayLater use, and financial attitude are all significant positive predictors of consumptive behavior. Crucially, financial literacy was found to be a significant negative moderator for the Shopee PayLater-consumption pathway, demonstrating its regulatory power in the context of targeted credit products. However, its moderating effect on the general FinTech-consumption link was not significant, suggesting that broad digital tool adoption may influence spending through channels beyond rational financial assessment. This nuanced outcome aligns with the post-positivist view that human behavior is complex and not fully determined by rational knowledge alone. These findings offer critical insights for policymakers and financial educators, indicating that literacy interventions may be most effective when specifically tailored to the mechanisms of popular BNPL services rather than digital finance in general.